Investigations on mechanical properties of Al6061-SiC nanocomposites fabricated via stir casting process. (2021) - Prakash, B.; Manimaran, M.
Abstract: Aluminium metal matrix composite (AMC's) gives a large impact in the field of applications of the military, and aerospace due to their improved mechanical and physical properties. The present work investigates the effects of adding Silicon Carbide (SiC) to Al6061 alloy. The percentage of SiC was varied by 3, 5, 7 wt%. The composites were fabricated by the stir casting process. The fabricated composites were analyzed for morphological and mechanical tests. From the results, it was found that the addition of SiC by 7 wt% resulted in enhanced properties.